2018
DOI: 10.1109/tvcg.2017.2744278
|View full text |Cite
|
Sign up to set email alerts
|

Abstractocyte: A Visual Tool for Exploring Nanoscale Astroglial Cells

Abstract: This thesis presents the design and implementation of Abstractocyte, a system for the visual analysis of astrocytes, and their relation to neurons, in nanoscale volumes of brain tissue. Astrocytes are glial cells, i.e., non-neuronal cells that support neurons and the nervous system. Even though glial cells make up around 50 percent of all cells in the mammalian brain, so far they have been far less studied than neurons. Nevertheless, the study of astrocytes has immense potential for understanding brain functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…Neuroscientists normally use standard surface visualization frameworks, like Blender, for performing visual inspection of neural structures decorated with glygogen distribution, in a way to speculate about proximity patterns and formulate hypothesis, even with the help of VR setups [CBB *16]. Recently, these surface rendering frameworks were enriched by highlighting absorption on surface reconstructions ( GLAM , proposed by Agus et al [ABG*18]), or by mapping glycogen content in abstract neurite representations ( Abstractocyte , proposed by Mohammed et al [MAAB*18]). After analysis sessions, neuroscientists concluded that all the frameworks can be considered complementary tools, since they provide different view of the same data.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Neuroscientists normally use standard surface visualization frameworks, like Blender, for performing visual inspection of neural structures decorated with glygogen distribution, in a way to speculate about proximity patterns and formulate hypothesis, even with the help of VR setups [CBB *16]. Recently, these surface rendering frameworks were enriched by highlighting absorption on surface reconstructions ( GLAM , proposed by Agus et al [ABG*18]), or by mapping glycogen content in abstract neurite representations ( Abstractocyte , proposed by Mohammed et al [MAAB*18]). After analysis sessions, neuroscientists concluded that all the frameworks can be considered complementary tools, since they provide different view of the same data.…”
Section: Resultsmentioning
confidence: 99%
“…After analysis sessions, neuroscientists concluded that all the frameworks can be considered complementary tools, since they provide different view of the same data. The main difference of our framework is that it works directly on EM volume data, that we use to compute the absorption information more accurately than the models proposed by Agus et al [ABG*18] and Mohammed et al [MAAB*18]. Figure left shows similar structures represented with Abstractocyte [MAAB*18](left) and the proposed framework (right): in this case a Multi Synaptic Bouton from mouse 3 connected to a dendrite.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations